(untitled) (Anais do Congresso Brasileiro de Processo Coletivo e Cidadania, 2020)
The Federal Government of Brazil has announced the implementation of a National Program of Civic-Military Schools. The mix of militarism and education is not new in the country and similar projects exist in some states of the Federation. This article aims to understand the objectives and purposes of education and the Armed Forces in the Federal Constitution and the challenges posed to education today. It is also intended to analyze the militarization of education in the face of the citizenship and democracy project presented by the 1988 Constitution. Education and the Armed Forces have distinct objectives and missions established by the Constitution. If the Armed Forces is presented with the primary challenge of defense of the country, education has as its mission the full development of the person and preparation for citizenship. The challenges posed by the new times require education professionals - who must be valued - new and innovative answers, and in this sense do not seem to be the most appropriate military techniques to achieve these goals.